Upaya Peningkatan Kesadaran Pendidikan Melalui Program Belajar Asik di Desa Karangsari, Sapuran, Wonosobo - Putranto, M. Dzaky; Sumitro, Wilal; Hafizh R, Reva; Rosid, Abdul; Sari, Indaah Kumala; Mustofa, M. Zainil; Nanda A, Desca; Trijaya, M. Kurnia; Aisah, Siti; Inderawan P, Danang; Rubiyanto, Cahyo Wisnu (Universitas Muhammadiyah Yogyakarta, 2025)
A prevailing social phenomenon in Karangsari Village, Sapuran, Wonosobo, is the high rate of labor migration, where most young people choose to migrate to urban areas in pursuit of employment opportunities deemed more profitable than pursuing higher education. The community's mindset, which prioritizes work over continued education, prompted the implementation of an education-based community service program called Belajar Asik (Basik). This mindset has led to limited public knowledge, particularly in financial management. The Basik program comprises two activities: classroom learning for kindergarten students and financial management socialization for the community. The program aims to enhance motivation regarding the importance of education from an early age through enjoyable learning experiences and to improve public understanding of financial management, thereby encouraging greater motivation to pursue higher education. The methods employed in this community service include socialization combined with focus group discussions and hands-on practice. The outcomes of this initiative include the creation of enjoyable learning experiences that foster more meaningful educational engagement and enhance student creativity, cultivating skills and a desire to continue schooling. Additionally, this community service has led to increased public understanding of financial management and the application of household financial planning in daily life